Competition policy in the FTAA: progress in the working group - Aráoz F., Mercedes; Van Ginhoven R., Sandra (Universidad del Pacífico, 2000)
The objective of the Free Trade Area of the Americas (FTAA) is to unite the thirty four economies of the Hemisphere into a single market. The negotiations are supposed to be completed by the year 2005. Though year 2000 is crucial since all the negotiated issues will be settle in the agenda. Initially, twelve working groups were established and, later, transformed into nine negotiation groups. Competition Policy is one these negotiation groups and it is probably the issue that would have long lasting effects over the behavior of firms among and within the FTM economies. This paper discusses why and how Competition Policy is included in the FTM. The removal of domestic entry barriers must be accompanied by the removal of private barriers, so equitable conditions for competitors throughout the Hemisphere are provided. Though, it is shown that there are dissimilar conditions among countries in the Hemisphere in terms of competition policy application. That is, not all countries have competition legislation and competition institutions; and for those who have, provisions, implementation and enforcement also differ. The Peruvian experience on this matter is presented and some policy recommendations for the negotiation process are included.